A novel protein CtCBP-1 functions as a crucial macromolecule during mineralization of limpet teeth - Wang, Yadong; Zhang, Rongqing; Liu, Chuang (Frontiers in Marine Science, 2022)
Limpets are a class of marine mollusks that use mineralized teeth, one of the hardest and strongest biological materials, to feed on algae on rocks. By combining proteomics and RNA-seq analysis of limpet radula, we identified a novel chitin-binding protein (CtCBP-1) that may play a regulatory role in radula mineralization of Cellana toreuma. In this study, the full-length cDNA of CtCBP-1 gene was cloned for the first time, and the protein was successfully expressed in vitro. In vitro experiments demonstrated that CtCBP-1 binds well to both goethite and chitin, which are key components of the cusp. We studied the function of CtCBP-1 on goethite crystallization in vitro, revealing that it changed the morphology of goethite crystals. We also used fluorescence super resolution imaging to map the binding of CtCBP-1 in radula and found that the distribution of CtCBP-1 on radula was specific, which consistent with the SEM results finding tightly aligned goethite. This study identifies for the first time a novel protein, CtCBP-1, that plays a regulatory role in the unique biomineralization process of limpet teeth, which may guide biomimetic strat-egies aimed at designing hard materials at room temperature.